Supporting The Development of Visually Impaired Children's Talents At SMP N 22 Surakarta - Lathifah, Dea Nisrina Nur (GRAB KIDS: Journal of Special Education Need, 2025)
This study aims to explain the provision of supporting facilities and the role of teachers in building the potential of blind children with special needs at SMP Negeri 22 Surakarta. The method used is descriptive qualitative by collecting data through interviews, observation and documentation. The research findings show that the school has provided adequate facilities both in terms of physical (such as good lighting, accessibility of disability-friendly pathways, and space for consultation) and non-physical (support in extracurricular activities and inclusive ways of learning). Teachers function as facilitators, motivators, intermediaries and companions who actively help students understand the material and develop their singing talents. Adequate facilities and sensitive teacher approaches have been shown to increase the enthusiasm, participation and confidence of visually impaired students in inclusive settings. This study emphasizes the importance of collaboration between available facilities and the role of teachers in inclusive education.